The twin transition under resource constraints: A proposed conceptual model for digital and green capability convergence - Pham, Tung Minh (Edelweiss Applied Science and Technology, 2026)
This study proposes an integrated framework to demystify the strategic mechanisms through which enterprises in transitional economies achieve digital and green capability convergence (the “Twin Transition”) despite severe resource constraints. To achieve this, the conceptual paper develops a theoretical model grounded in Resource Orchestration Theory and the Theory of Bricolage, outlining a quantitative survey design targeting top management with data analysis proposed via Consistent Partial Least Squares Structural Equation Modeling (PLSc-SEM). Specifically, the model posits that Resource Orchestration Capability acts as a core mediating mechanism transforming Digital Technology and Green Innovation Capabilities into Strategic Agility and Competitive Advantage. Furthermore, Bricolage Capability is integrated as a vital moderating variable that empowers organizations to navigate financial deficits effectively. Ultimately, the paper concludes that resource scarcity is not an insurmountable barrier; rather, when orchestrated through a bricolage mindset, it paradoxically acts as a catalyst for breakthrough twin transition innovation. As a result, the framework offers actionable insights for SME executives in emerging markets, suggesting that leveraging low-cost assets through bricolage enables them to meet stringent global sustainability and digital standards without heavy capital investments.